2016
DOI: 10.1124/dmd.116.071902
|View full text |Cite|
|
Sign up to set email alerts
|

Tramadol Metabolism toO-Desmethyl Tramadol (M1) andN-Desmethyl Tramadol (M2) by Dog Liver Microsomes: Species Comparison and Identification of Responsible Canine Cytochrome P450s

Abstract: Tramadol is widely used to manage mild to moderately painful conditions in dogs. However, this use is controversial since clinical efficacy studies in dogs showed conflicting results, while pharmacokinetic studies demonstrated relatively low circulating concentrations of O-desmethyltramadol (M1). Analgesia has been attributed to the opioid effects of M1, while tramadol and the other major metabolite (N-desmethyltramadol, M2) are considered inactive at opioid receptors. The aims of this study were to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 38 publications
4
40
0
3
Order By: Relevance
“…As a result of impaired glucuronidation in this species, the isoform M1 tends to persist for longer periods in cats than in dogs (CAGNARDI et al, 2011). Additionally, the rate of M1 formation by liver microsomes of cats are 3.9 times faster than that observed in dogs (PEREZ et al, 2016). The significant reduction of PD values observed from the middle time point to the end of our experiment suggested that tramadol is able to sustain mydriasis in cats for at least 2 hours.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…As a result of impaired glucuronidation in this species, the isoform M1 tends to persist for longer periods in cats than in dogs (CAGNARDI et al, 2011). Additionally, the rate of M1 formation by liver microsomes of cats are 3.9 times faster than that observed in dogs (PEREZ et al, 2016). The significant reduction of PD values observed from the middle time point to the end of our experiment suggested that tramadol is able to sustain mydriasis in cats for at least 2 hours.…”
supporting
confidence: 48%
“…In humans, the pupillary response to tramadol is influenced by the genotype CYP2D6, which encodes isoenzymes that metabolize tramadol to its active metabolite (M1) (MATOUSKOVAet al, 2011). Thus, individuals that do not express such genotype tend to develop mydriasis when treated with tramadol; while the ones that express CYP2D6, miosis was observed (PEREZ et al, 2016). Regarding the pharmacokinetics Figure 1 -Mean values ± standard error of pupil diameter (mm) (A) and intraocular pressure (mmHg) (B) before (baseline) and after 15, 30, 60 and 120 minutes of the intramuscular administration of acepromazine, tramadol and the combination acepromazine and tramadol in young healthy cats.…”
mentioning
confidence: 99%
“…O principal metabólito do tramadol reconhecidamente responsável pela analgesia em nível de receptores opioides é o O-desmetiltramadol (M1) (Kukanich & Papich 2004, 2011. A produção deste metabólito em cães é realizada pelo grupo de enzimas hepáticas citocromo P450, subtipo 2D15 a qual sofre polimorfismo individual em cães, fazendo com que a produção deste metabólito apresente uma grande variação individual nessa espécie (Giorgi et al 2010, Perez et al 2016, o que faz com que a concentração circulante do M1 em cães seja menor do que em humanos e gatos o que justifica menor eficiência analgésica (Perez et al 2016), além de explicar também a diferença individual quanto aos efeitos do tramadol em diferentes cães (McMillan et al 2008, Kogel et al 2014, Goudie-Deangelis & Woodhouse 2015, o que provavelmente acontece na prática clínica e refletiu no presente estudo. Embora alguns estudos comprovaram a eficácia analgésica do tramadol no pós-operatório de diferentes tipos de cirurgia (Yazbek & Fantoni 2005, Buhari et al 2012, a sua real aplicação, nas doses aqui estudadas, no pós-operatório de cirurgias que envolvem a coluna vertebral ainda é questionável, necessitando de estudos controlados direcionados à avaliação de dor após esse tipo de procedimento em cães.…”
Section: Resultsunclassified
“…Among these methods, HPLC-MS/MS method has been adopted extensively in the recent years due to the highselectivity, high-sensitivity, and high-speed separations, but reference standards of the analyzed metabolites are required for the quantication. [24][25][26][27][28] In our study, reference standards of the two metabolites were synthesized or puried in our laboratory, and the structures were conrmed using nuclear magnetic resonance (NMR) as described previously. 2 The purities of these two metabolites were determined by HPLC method to be above 99.0%.…”
Section: Discussionmentioning
confidence: 99%